123 Coronary imaging of cardiac allograft vasculopathy predicts current and future deterioration of left ventricular dysfunction in patients with orthotopic heart transplantation. (4th June 2021) - Reddy, Ashwin; Khialani, Bharat; Lambert, Ben; Flore, Vincent; Brown, Adam; West, Nick; Pettit, Stephen; Parameshwar, Jayan; Lewis, Clive; Bhagra, Sai; Kydd, Anna; Hoole, Stephen
Abstract : Background: Cardiac allograft vasculopathy (CAV) is the leading cause of morbidity and mortality in heart transplant patients beyond the first post-transplant year, accounting for approximately 30% of all-cause mortality in this patient group. The incidence of CAV is 47% at 10 years post-transplant, though it can occur within the first year. Early detection of CAV is vitally important as modifications to medical therapy may slow progression of CAV and thus prevent downstream graft dysfunction. Intravascular Ultrasound (IVUS) and Optical Coherence Tomography (OCT) improve sensitivity of CAV detection compared to invasive coronary angiography (ICA), but the respective ability of each modality to predict downstream clinical events is unknown. Furthermore, whilst OCT has been shown to provide additional information about coronary vascular endothelial properties there is no consensus as to what constitutes 'severe' CAV on OCT, thus limiting its diagnostic utility.We sought to determine:1) The ability of OCT to diagnose CAV compared to IVUS, and determine a set cut-point for diagnosing 'severe' CAV on OCT.2) Whether severe CAV detected with ICA, IVUS or OCT correlates with future clinical events and graft function. Methods: Comparison of specific vessel parameters between IVUS and OCT on 20 patients attending for routine surveillance angiography 12-24 months post-orthotopic heart transplant. Major adverse cardiac events (MACE) and serial left ventricular ejection fraction were recorded prospectively.Comparisons of continuous data were performed using unpaired Student's t-tests and analysis of variance (ANOVA), whilst categorical data were compared using the χ2 test. A two-tailed probability level of <0.05 was considered significant. Results: Baseline demographic data for the 20 patients are shown in table 1 . Analyzing 55 coronary arteries we demonstrate that OCT and IVUS correlated well for vessel CAV characteristics ( figure 1 ), although measured values were significantly smaller on OCT: mean intimal thickness (IT) by OCT was 0.21±0.1mm vs 0.44±0.24 mm by IVUS, p <0.001. A mean ITOCT >0.25mm had a sensitivity of 86.7% and specificity of 74.3% at detecting Stanford grade 4 CAV. Those with CAV evident on ICA had significant reduction in graft ejection fraction (EF) over median follow up of 7.3 years (mean ΔEF -3.6% with CAV vs +3.8% without CAV, p=0.04). Patients with mean ITOCT >0.25mm in at least one vessel had a lower EF at time of surveillance (55.9% vs 61.1%, p=0.0007) ( figure 2 ). Only two MACEs were noted. Conclusion: Coronary imaging with OCT correlates well with IVUS for detection of CAV. Mean IT of >0.25mm on OCT detects Stanford grade 4 CAV with reasonable accuracy and may be a useful cut-point for clinical use.Combined angiography and OCT to screen for CAV within 12-24 months of transplant predicts concurrent and future deterioration in left ventricular function, thus may trigger early alterations to clinical management to prevent clinical worsening. Conflict of Interest: none